Feasibility Study of Sustainable Energy to Power Wastewater Treatment Plants for Islands - Gunbold Gunnar Bold 1984- (2014)
Samvinnuverkefni Verkfræði- og náttúruvísindasviðs og Keilis Municipal wastewater treatment plays a critical role in protecting local water quality and public health. Wastewater treatment is very energy intensive as it involves operation of large motors, drives, pumps and other equipment on a 24 hour-a-day basis. Improving quality of sewage treatment to produce more environmentally safe effluent requires more energy. Conventional energy sources such as oil, gas and coal are non-renewable. The use of fossil fuel has a significant health and environmental impact. This study discusses the opportunities of using renewable energy sources and self-sufficiency options for wastewater treatment plants (WWTP). The study focuses on applying solar and wind energy, and on site produced biogas to meet the energy requirement and to eliminate emissions from fossil fuel. Two facilities are presented as case study, Kailua, located on the island of Oahu, Hawaii and Hveragerði, located in Iceland. Electricity consumption of the plants was analyzed and the HOMER Energy software was used to evaluate the cost of electricity ($/kWh) of various energy system configurations, each with their own combination of equipment. The objective was to determine the optimal hybrid renewable energy system (HRES). The hybrid system consists of solar PVs, wind turbines and combined heat and power (CHP) unit. A detailed cost and component size evaluation was done for the hybrid system and it showed that renewable energy source can fully and safely power the facilities. The result suggested that it is economically viable to apply the HRES in Kailua WWTP. Compared with the current electric supply rate (0.29 $/kWh), the HRES unit could reduce the tariff to 0.17 $/kWh. On the other hand, the HRES alternative was not feasible for Hveragerði facility. It costs 1.14 $/kWh to generate electricity, compared to the current rate, 0.12 $/kWh.